Գաբրիել Այվազյանի «Բառազննութիւն աշխարհիկ լեզուի» ձեռագիր երկը՝ որպես աշխարհաբարի տարածմանը նպաստող աշխատություն - Իրիցյան, Հասմիկ
G. Ayvazyan’s handwritten work “Word-study of the secular Language” (Ms M 2878) gives an idea of his role in the spread of ashkharhabar (the New Armenian language) and is an interesting sample of dictionary. Having grounded the development of the New Armenian by theoretical provisions in his earlier articles, in the work in question the author attempts to put the New Armenian of his day into use. G. Ayvazyan offers authors with a sort of handbook for Armenian vocabulary, in order to make their works accessible for wide circles. The manuscript contains Ayvazyan’s interesting linguistic observations and characteristics, as well as his arguments in favour of giving preference to Ashkharhabar. Besides it provides information on a specific sample of the mid 19th century Armenian, which makes our knowledge of the Armenian vocabulary of that period more accurate. Рукописный труд Габриэла Айвазяна (Айвазовского) “Анализ слов светского языка” (рукопись № 2878 из собрания Матенадарана им. М. Маштоца) дает представление о роли Г. Айвазяна в распространении ашхара-бара (новоармянского языка), являясь интересным образцом словаря. Обосновав в ранее опубликованных статьях развитие ашхарабара теоретическими положениями, в рассматриваемом труде автор пытается ввести новоармянский язык в обиход. Г. Айвазян предлагает авторам как бы руководство по лексике армянского языка, с целью сделать их тексты доступными широкой общественности. Рукопись содержит интересные языковые наблюдения и характеристики Г. Айвазяна и аргументы в пользу предпочтения ашхарабару. Кроме того, она знакомит нас с конкретным образцом ашхарабара середины XIX века, уточняя наши представления о словарном запасе новоармянского языка этого периода.
Keywords: Մխիթարյան միաբանություն; Ձեռագրեր; Բառարան; Աշխարհաբար; Գրաբար